2016
DOI: 10.1177/1553350615624789
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy Versus Robotic Surgery for Colorectal Cancer

Abstract: Background Minimally invasive approach has gained interest in the treatment of patients with colorectal cancer. The purpose of this study is to analyze the differences between laparoscopy and robotics for colorectal cancer in terms of oncologic and clinical outcomes in an initial experience of a single center. Materials and Methods Clinico-pathological data of 100 patients surgically treated for colorectal cancer from March 2008 to April 2014 with laparoscopy and robotics were analyzed. The procedures were rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 33 publications
0
26
1
Order By: Relevance
“…However, generally, a longer operation time was reported for the robotic procedure. [ 1 3 , 7 9 , 11 , 13 , 14 , 19 , 26 , 33 , 34 ] In our study, the mean operation time was significantly longer in the Robot 1 group than in the LPS group. However, the mean operation time shortened markedly in the Robot 2 group, approaching that in the LPS group.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…However, generally, a longer operation time was reported for the robotic procedure. [ 1 3 , 7 9 , 11 , 13 , 14 , 19 , 26 , 33 , 34 ] In our study, the mean operation time was significantly longer in the Robot 1 group than in the LPS group. However, the mean operation time shortened markedly in the Robot 2 group, approaching that in the LPS group.…”
Section: Discussionmentioning
confidence: 42%
“…The quality of the surgical specimen and the long-term oncological outcomes of laparoscopic surgery are equivalent to those of open surgery; however, recovery, physiological function, and other short-term outcome measures improve after laparoscopic surgery. [ 1 4 ] However, laparoscopic surgery for rectal cancer is technically demanding, limiting its application in nonspecialized centers. The anatomical confinement of the deep pelvis, restricted movement of the rigid instruments, amplification of the tremor from the fulcrum effect, and unstable image provided by the hand-held camera contribute to the difficulty of this procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Completeness of resection and mean distal resection margin were reported in five studies, with three studies reporting complete (R0) resection achieved for all robotic and laparoscopic patients . No study reported significant differences between surgical approaches.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Laparoscopic surgery (LS) for colon cancer has a wide use due to its beneficial properties and has prevailed compared with open surgery. [9][10][11][12][13][14][15] However, robotic surgery (RS) has been recently introduced as a new contemporary alternative because of its obvious advantages, including the three-dimensional view, the ability to use multidegree-of-freedom forceps, the elimination of physiological tremors, and the stable camera control, in order to broaden the horizons of MIS.…”
mentioning
confidence: 99%